The diversity of undergrowth plants on Acacia nilotica stands as food resources of banteng (Bos javanicus) in Baluran National Park, East Java, Indonesia - DJUFRI DJUFRI; WARDIAH WARDIAH (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Djufri, Wardiah. 2017. The diversity of undergrowth plants on Acacia nilotica stands as food resources of banteng (Bos javanicus) in Baluran National Park, East Java, Indonesia. Biodiversitas 18: 288-294. The objectives of this research were to determine species composition, importance value of species, diversity index and evenness index of the undergrowth plants of Acacia nilotica stands. The quadratic method was used in this study. The similarity indeks and cluster analysis were performed to classify the community structure of undergrowth plants of Acacia nilotica. The results of this study showed that there were 63 species of plant belonging to 18 families. The importance value ranged between 0.97-42.58 and high and medium importance values belonged to Brachiaria reptans, Thespesia lampas, Oplismenus burmannii, Dichanthium coricosum, Axonopus compressus, and Synedrella nodiflora. The diversity index and evenness ranged 1.1504-2.7556 and 1.1067-1.7854, respectivelly. The Brachiaria reptans, Dichantium coricosum, Thespesia lanpas, Achyrantes aspera, Stachytarpeta indica, Axonopus compressus and Oplismenus burmanii were predominant in study area. In addition the invasion of A. nilotica has decreased the carryng capacity of savanna in Baluran National Park to the banteng. Keywords: Acacia nilotica, species composition, banteng, Baluran National Park